Comparison of single- and double-balloon catheters for labor induction: a systematic review and meta-analysis of randomized controlled trials. (March 2018) - Salim, Raed; Schwartz, Naama; Zafran, Noah; Zuarez-Easton, Sivan; Garmi, Gali; Romano, Shabtai
Abstract Objective There is a paucity of head-to-head randomized trials that compare single- and double-balloon catheters, and the results of the available data in terms of time from catheter insertion to delivery and delivery mode are mixed. This meta-analysis of randomized controlled trials compares the efficacy of single- and double-balloon catheters in women undergoing labor induction. Study design Searches were made in MEDLINE, EMBASE, PubMed, ClinicalTrials.gov, and the Cochrane Library from inception through June 2016. Peer-reviewed randomized and quasi-randomized trials that compared single- and double-balloon catheters head-to-head for cervical ripening or labor induction were identified. Eligible study populations consisted of women with singleton pregnancies that had any indication for labor induction and were randomly assigned to undergo induction with a single- or a double-balloon catheter. The primary outcome was time from catheter insertion to delivery and delivery mode. The secondary outcomes were intrapartum fever or chorioamnionitis, woman's satisfaction, and neonatal Apgar score. Results Of the 520 records identified, five randomized trials (996 women; 491 with single-balloon and 505 with double-balloon catheters) were considered eligible and included in the meta-analysis. Time from catheter insertion to delivery did not differ between the two types of catheter (p  = 0.527; WMD −0.87; 95% CI: −3.55, 1.82). The incidence of cesarean delivery also did not differ (p  = 0.844; RR 0.97; 95% CI: 0.69, 1.35). Delivery within 24 h, delivery mode, incidences of intrapartum fever or chorioamnionitis, and neonatal Apgar score <7 at 5 min did not differ between the two types of catheter as well. Women who were induced with the single-balloon catheter were more satisfied (p  = 0.029; WMD 0.56; 95% CI: 0.06, 1.06). Conclusion Time from catheter insertion to delivery and delivery mode were comparable between the two types of catheter.